A case of bilateral absence of carotid canals in human skull - Khan, Aaijaz Ahmed; Asari, Mohd. Asnizam; Pasha, Mehboob Alam (Bangladesh Journal of Medical Science, 2016)
Anatomical variation in the lower limb was found during routine dissection in a 75-year-old male cadaver in the Morphology Laboratory at the University of Pamplona. While examining 25 skulls present in the department of Anatomy, Universiti Sains Malaysia, we found that in one of the skull the floor of the carotid canal was absent on both the sides. The absence of the floor, exposed the roof of the carotid canal which appeared as a deep groove extending on the under surface of the petrous temporal bone. Following review of literature, we found that absence of the carotid canal is a very rare anomaly and has a great clinical importance. Exposed internal carotid artery in the absence of floor can make it at risk of injury during skull base surgeries. Therefore, we decided to report this case. Bangladesh Journal of Medical Science Vol.15(2) 2016 p.275-277